2010
DOI: 10.1159/000284466
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intravitreal Bevacizumab versus Triamcinolone for the Treatment of Diffuse Diabetic Macular Edema

Abstract: Background: Our purpose was to compare the effect of triamcinolone and bevacizumab (Avastin) on the retinal thickness and functional outcome in patients with diabetic macular edema. Methods and Materials: A collective of 32 patients, who had been treated by a single 4.0-mg intravitreal triamcinolone injection (group 1), was matched to 32 patients (‘matched pairs’), who had received 3 injections of 1.25 mg of bevacizumab within 3 months in 4-week intervals (group 2). The outcome variables were changes in best c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 59 publications
1
12
0
2
Order By: Relevance
“…A second level of scrutiny (generally removing case reports, in which the data were not presented in the way defined as suitable et cetera) reduced this further to a total of 140 cohorts reported in 121 different publications, of which only 88 were found to include a full set of data for the planned analyses comparing CMT to VA. The reasons for exclusion were generally because of an incomplete data set (for example, by just reporting percentage changes or the fraction of eyes with a certain range of changes in VA or CMT), leaving 43, nine, 18 and 17 data sets of information for the different interventions (Table ) with some publications yielding more than one set of data …”
Section: Resultsmentioning
confidence: 99%
“…A second level of scrutiny (generally removing case reports, in which the data were not presented in the way defined as suitable et cetera) reduced this further to a total of 140 cohorts reported in 121 different publications, of which only 88 were found to include a full set of data for the planned analyses comparing CMT to VA. The reasons for exclusion were generally because of an incomplete data set (for example, by just reporting percentage changes or the fraction of eyes with a certain range of changes in VA or CMT), leaving 43, nine, 18 and 17 data sets of information for the different interventions (Table ) with some publications yielding more than one set of data …”
Section: Resultsmentioning
confidence: 99%
“…Single IVT (4 mg) was reported to show a more rapid and greater effect, compared with single IVB [17,18], and it was reported that there was no difference between 3 subsequent IVB injections and single IVT (4 mg) on DME [19]. In this study, IVT (2 mg) with/without bevacizumab showed a more pronounced effect on visual acuity and reduction of macular edema, compared with twice IVB within the earlier period (6 weeks, 3 months), and the difference had disappeared at 6 and 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Fixed treatment guidelines for DME have not been determined, and the variable combination therapy of intravitreal drugs, such as anti-VEGF or corticosteroid with/without laser photocoagulation, were considered and were tried for the treatment of DME, dependent on the physician. However, comparative studies on DME were limited to analysis of the short-term effects [11,14,17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…2009). The clinical effect of a single IVT is comparable to three injections of bevacizumab (Kreutzer et al. 2010).…”
Section: Baseline Characteristics (N = 140)mentioning
confidence: 99%